Hybrid Integrated Nanophotonic Silicon-based Structures - Hoang, Thi Hong Cam; Pham, Thanh Binh; Nguyen, Thuy Van; Pham, Van Dai; Bui, Huy; Pham, Van Hoi; Duran, Elena; Ramos, Carlos; Roux, Xavier Le; Vivien, Laurent; Cassan, Eric (Communications in Physics, 2019)
We report nanophotonic silicon-based devices for hybrid integration: 1D photonic crystal (PhC) on optical fiber, i. e. fiber Bragg grating (FBG) sensing probe integrated in fiber laser structure for chemical sensors and slotted planar 2D PhC cavity combined with carbon nanotube (CNT) towards light nanosources. The experiments have been carried out by integrating 1D PhC on optical fiber in fiber laser structure. This structure possesses many advantages including high resolution for wavelength shift, high optical signal-to-noise ratio (OSNR) of about 50~dB, the small full width at half-maximum (FWHM) of about 0.014~nm therefore its accuracy is enhanced, as well as the precision and capability are achieved for remote sensing. Low nitrate concentration in water from 0 to 80 ppm has been used to demonstrate its sensing ability in the experiment. The proposed sensor can work with good repeatability, rapid response, and its sensitivity can be obtained of \(3.2× 10^{ - 3}\) nm/ppm with the limit of detection (LOD) of 3~ppm. For 2D PhC cavity, enhancement of photoluminescence of CNT emission is observed. The semiconducting single-walled carbon nanotubes (s-SWNTs) solution was prepared by polymer-sorted method and coupled with the confined modes in silicon slotted PhC cavities. The enhancement ratio of 1.15 is obtained by comparing between the PL peaks at two confined modes of the cavity. The PL enhancement result of the integrated system shows the potential for the realization of on-chip nanoscale sources